In Silico Study of Bay Leaf (Syzygium polyanthum) Compounds as Renin Inhibitors and Antihypertensive Herbal Tea Development - Blegoh Iwan Santoso; Siti Nur Hikmah; ahmad Robitah; Khrisna Agung Cendikiawan; Kintoko (Jurnal Kesehatan dr. Soebandi, 2026)
Background :  Hypertension is a major global health problem contributing significantly to cardiovascular morbidity and mortality. One of the key pathways in blood pressure regulation is the Renin–Angiotensin– Aldosterone System (RAAS), where renin plays a crucial role as the initiating enzyme. Inhibition of renin is considered a more specific therapeutic strategy with potentially fewer side effects. Bay leaf (Syzygium polyanthum) has been traditionally used as an antihypertensive agent and contains various bioactive compounds Methods : This study aims to evaluate the potential of bay leaf compounds as renin inhibitors using an in silico approach and to explore their development into herbal tea products. Active compounds were identified through literature-based LC-MS data, including gallic acid, malic acid, luteic acid, and myricetin. Molecular docking was performed using AutoDock Vina against human renin (PDB ID: 3D91). Results: The results showed that myricetin exhibited the highest binding affinity (-9.3 kcal/mol), followed by luteic acid (-7.9 kcal/mol), gallic acid (-6.1 kcal/mol), and malic acid (- 5.1 kcal/mol), compared to the standard inhibitor remikiren (-10.3 kcal/mol). Conclusions: Interaction analysis revealed that myricetin formed multiple hydrogen bonds with catalytic residues. These findings suggest that bay leaf compounds, especially myricetin, have potential as natural renin inhibitors and could be developed as antihypertensive herbal tea.